PERAN SERTA PEMERINTAH DAN MASYARAKAT DALAM MENCEGAH TINDAK PIDANA PORNOGRAFI - Liza Deshaini; Kinaria Afriani (Fakultas Hukum Universitas IBA Palembang, 2019)
The government's participation in the prevention of pornography crimes is cut off the network for making and disseminating pornographic products or pornographic services, including the blocking of pornography through the internet, supervise the making, dissemination and use of pornography and, cooperate and coordinate with various parties, both from within and outside the country, in preventing the creation, dissemination and use of pornography. and the public in the prevention of criminal acts of pornography are reporting violations of this law, filing lawsuits to court, socializing legislation that regulates pornography, and providing guidance to the community on the dangers and impacts of pornography.